Pharmacological and non-pharmacological therapeutic interventions for the treatment of spinal cord injury-induced pain - Eller, Olivia C.; Willits, Adam B.; Young, Erin E.; Baumbauer, Kyle M. (Frontiers in Pain Research, 2022)
Spinal cord injury (SCI) is a complex neurophysiological disorder, which can result in many long-term complications including changes in mobility, bowel and bladder function, cardiovascular function, and metabolism. In addition, most individuals with SCI experience some form of chronic pain, with one-third of these individuals rating their pain as severe and unrelenting. SCI-induced chronic pain is high impact, affecting daily activity, physical and cognitive function, mood, sleep, and overall quality of life. The majority of SCI pain patients suffer from pain that emanates from regions located below the level of injury. This pain is often rated as the most severe and the underlying mechanisms involve injury-induced plasticity along the entire neuraxis and within the peripheral nervous system. Unfortunately, current therapies for SCI-induced chronic pain lack universal efficacy. Pharmacological treatments, such as opioids, anticonvulsants, and antidepressants, have been shown to have limited success in promoting pain relief. In addition, these treatments are accompanied by many adverse events and safety issues that compound existing functional deficits in the spinally injured, such as gastrointestinal mobility and respiration. Non-pharmacological treatments are safer alternatives that can be specifically tailored to the individual and used in tandem with pharmacological therapies if needed. This review describes existing non-pharmacological therapies that have been used to treat SCI-induced pain in both preclinical models and clinical populations. These include physical (i.e., exercise and hyper- or hypothermia treatments), psychological (i.e., meditation and cognitive behavioral therapy), and dietary interventions (i.e., ketogenic and anti-inflammatory diet). Findings on the effectiveness of these interventions in reducing SCI-induced pain and improving quality of life are discussed. Overall, although studies suggest non-pharmacological treatments could be beneficial in reducing SCI-induced chronic pain, further research is needed. Additionally, because chronic pain, including SCI pain, is complex and has both emotional and physiological components, treatment should be multidisciplinary in nature and ideally tailored specifically to the patient.